2015
DOI: 10.1111/vop.12294
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective evaluation of corneal reconstruction usingACell Vetalone in dogs and cats: 82 cases

Abstract: Corneal reconstruction with ACell Vet(™) alone is a viable alternative and results in minimal scarring and complications in cats. In dogs, scarring is more pronounced than in cats and graft dehiscence rate is higher compared to conventional techniques.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
60
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(66 citation statements)
references
References 77 publications
5
60
0
1
Order By: Relevance
“…In veterinary medicine it has been reported for use in corneal reconstruction in dogs and cats (Balland et al . ; Chow and Westermeyer ) and for severe ulceration with keratomalacia in horses (Mancuso et al . ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In veterinary medicine it has been reported for use in corneal reconstruction in dogs and cats (Balland et al . ; Chow and Westermeyer ) and for severe ulceration with keratomalacia in horses (Mancuso et al . ).…”
Section: Discussionmentioning
confidence: 99%
“…Studies in the dog and cat have demonstrated that vascularisation of A cell grafts is usually evident around the second week and that epithelialisation is usually complete by the third week (Chow and Westermeyer ). In contrast, in the equine case reported here, epithelialisation was still incomplete at 3 weeks.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the studies presented by Mancuso et al . (), Chow and Westermeyer () and Balland et al . (), the overall success rate for the use of UBM alone in ulcerative keratitis was >80%, in terms of the retention of a comfortable and visual eye.…”
Section: Introductionmentioning
confidence: 95%
“…UBM can also be used as a sole therapy, as has been reported in dogs and cats with varying degrees of ulcerative keratitis, including corneal perforation (Balland et al . ; Chow and Westermeyer ) and in horses with partial thickness ulcerative keratitis (Mancuso et al . ).…”
Section: Introductionmentioning
confidence: 99%